ARCHITECTURAL COMPLEX OF LVIV MEDICAL UNIVERSITY: HISTORY OF ESTABLISHMENT AND DEVELOPMENT (Південний архів (історичні науки), 2023)
The purpose of the study is the history of the development of the main stages of the design and construction of educational buildings, which have become the central premises for the study and training of medics at Lviv University. The methodological basis of the study became historiographical analysis and synthesis methods and historical-systemic method used under the principles of historical objectivism. The main results of the study. The study examines the process of founding Lviv University as one of the oldest in Ukrainian lands. Attention is drawn to the progress of secularization in the Austrian Empire, which provided an opportunity to use the fortunes of liquidated monastic orders for the needs of the state, in particular, the restoration of educational institutions in Lviv. The scientific investigation examines the process of the formation and development of the medical faculty into a medical university proper, as well as the possibility of using the old hospital premises of Lviv monasteries. Information is highlighted concerning the construction of new educational buildings for the medical faculty of Lviv University and educational premises where future medical professionals were trained at city medical institutions at the end of the 19th and 20th centuries. Conclusions. The presented information shows that the history of the design and construction of premises where medics studied is inextricably linked with the formation of the historical landscape of the city of Lviv during the 19th and 20th centuries. This period also provides an opportunity to analyze the changes that took place in the development of the city's infrastructure, especially in its eastern suburb – the Lychakiv district. The author of the study draws attention to the creative activity of famous European architects and constructors who participated in the design and construction of the city's medical institutions and educational buildings of the medical university. Their creative output makes it possible to trace the evolution of the use of architectural styles in Lviv from baroque to twentieth-century constructivism.
Keywords: education, Galicia, Lviv University, medical faculty, educational premises, architecture